Tingkat Kepuasan Wisatawan Domestik terhadap Candi Prambanan dan Ratu Boko di Kabupaten Sleman Daerah Istimewa Yogyakarta - Jemadi Jemadi; Bambang Sugeng Dwiyanto (Jurnal Maksipreneur, 2016)
This study will analyze the level of satisfaction of domestic tourists to Prambanan and Ratu Boko temple for services and facilities provided by Prambanan and Ratu Boko temple to domestic tourists consisting of entrance fee, temple beauty, service, security, and promotion from Prambanan temple And Ratu Boko who can make the tourists feel satisfied that encourages the desire to return again on another occasion. The population in this study were all visitors of Prambanan Temple and Ratu Boko Temple in Sleman District of Yogyakarta Special Region, and samples taken 100 people by using Accidental Sampling Method in sampling, that is make the sample of people who by chance found in the place of research. In this research showed that the level of satisfaction of domestic tourists to the temple of prambanan and queens boko based on entrance fee 3.72 (satisfied); The beauty of temple 4.40 (very satisfied); Service 3,50 (satisfied); Security 3.55 (satisfied); 3.20 promotion (less satisfied). In general, the satisfaction level is in the satisfied category because the mean value of aritmatic is 3.674 (satisfied). While the most dominant factor contributing to the level of domestic tourist satisfaction of prambanan temple and queens boko in Prambanan Sleman Yogyakarta is the beauty with arithmetic mean value 4.40 (very satisfied).